Prepositioness datives in Old and Middle Irish: the instrumental, accompaniment/inclusive and appositional dative - Lash, Elliott (Studia Celtica Posnaniensia, 2024)
The early Irish dative case is typically found after prepositions, but there are a number of nonprepositional usages. Three of these are explored in this chapter: the instrumental dative, the dative of accompaniment or inclusion, and the dative of apposition. The main goal of the chapter is to describe the syntactic distribution and features of these constructions, compare their similarities and differences, and ultimately to sharpen the classification of these three usages of the dative into distinct constructions. The bulk of the chapter concentrates on the third construction, the dative of apposition, in which the dative-marked nominal is found in apposition chiefly to a pronominal item. Because this pronominal is virtually obligatory, comparison between the early Irish appositional dative and a typology of similar “adnominal pronoun constructions” in other languages is made. A major contribution of the chapter is to show that there are various number and person restrictions that are placed on the pronominal antecedent but these restrictions are subject to diachronic variation. Finally, the dative of apposition is contrasted with the nominative of apposition, which is shown have a distinct syntactic structure.